Survei Tingkat Ketersediaan Sarana Prasarana dan Minat Bakat Siswa dalam Permainan Tenis Meja di SMA Negeri 10 Medan - Idhe Mafrael Sianturi; Yonaxel Jusak Rajagukguk; Indra David Sinaga; Gilbert Putra Imozen Saragih; Samsuddin Siregar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the level of availability of facilities and infrastructure as well as students’ interest and talent in table tennis at SMA Negeri 10 Medan. The focus of the study includes: (1) the condition and availability of table tennis facilities and infrastructure in schools, (2) the level of utilization of table tennis facilities in the learning process, (3) students’ interest in table tennis, and (4) students’ talent in participating in learning activities and table tennis sports activities. This research employed a quantitative descriptive method with a survey approach. The research subjects consisted of 30 students of SMA Negeri 10 Medan. Data collection techniques were carried out through observation, questionnaires, and documentation. The research instruments were prepared based on indicators of facilities and infrastructure, students’ interest, and talent in table tennis. Data analysis was conducted using percentage techniques to determine the research result categories. The results showed that the availability of table tennis facilities and infrastructure at SMA Negeri 10 Medan was categorized as good and supported the sports learning process at school. In addition, students’ interest in table tennis was also categorized as good, indicated by students’ enthusiasm in participating in learning and practical activities. Students’ talent in table tennis showed fairly good results, where several students demonstrated basic abilities that have the potential to be developed through more directed and continuous training. Therefore, it can be concluded that the availability of adequate facilities and infrastructure has a positive relationship with the improvement of students’ interest and talent in table tennis at SMA Negeri 10 Medan.